THE OPTIMIZATION OF THE ROLE BHAYANGKARA BUILDER OF SECURITY AND PUBLIC ORDER IN PREVENTING THE SPREAD OF RADICALISM THROUGH ACTIVE GUIDANCE AND EXPLANATION IN THE JURISDICTION OF THE SUKOHARJO POLICE - RAHMAT MULTAZAM HAMZAH (Police Studies Review, 2022)
Radicalism is an understanding that aims to change or replace the basis of the state into the basis of its own understanding. Radical understanding is very dangerous because it involves the ideology of a nation. In Indonesia, there are often cases of terrorism related to Sukoharjo Regency. Starting from perpetrators who are domiciled in Sukoharjo Regency to terrorist actors who have studied at one of the Islamic boarding schools in Sukoharjo. This study describes the spread of radicalism in the jurisdiction of the Sukoharjo Police. The purpose of this research is to describe the optimization and implementation of giat guidance and explanation by bhayangkara builder of security and public order of the Sukoharjo Police in preventing the spread of radicalism in the jurisdiction of the Sukoharjo Police. In optimizing activities and implementing guidance and explanation activities, which are a preventive measure for the spread of radicalism in Sukoharjo, members of the bhayangkara builder of security and public order are guided by the Chief of Police Regulation number 7 of 2021 concerning bhayangkara fostering security and public order and the Chief of Police Regulation number 21 of 2007 concerning guidance for counseling public security and order. The analytical knife used in describing the purpose of this research uses the theory and elements of management by George R. Terry, the approach used in this research is a qualitative approach and data collection through interview, observation, and document studies. Based on the discussion of the research results, it can be concluded that the implementation of coaching and counseling activities still needs to be optimized from the human element and the methods used in the implementation of coaching and counseling activities. In the implementation of coaching and counseling activities, there are also several inhibiting factors, especially at the implementation and supervision stages, so that the implementation of coaching and counseling activities by bhayangkara builder of security and public order in preventing the spread of radicalism in the jurisdiction of the Sukoharjo Police is not optimal.